Mediated Narration in the Digital Age : Storying the Media World - Gloviczki, Peter Joseph (Book collections on Project MUSE., 2021)
"Mediated Narration in the Digital Age examines mediated narration from 1991 through 2018. Peter Joseph Gloviczki considers this pivotal period spanning the rise of the World Wide Web through the growth of social media to understand how contemporary media accounts storied everyday life and times of crisis. He uses examples across media culture to show that complicated issues benefit from a critical post-structuralist approach to journalism, which promotes a communitarian ethos of respect, inclusion, and dialogue. Textual analysis of a wide range of media narratives-from a 2012 YouTube clip outlining a timeline of the Sandy Hook school shootings, to coverage of then-newly-discovered footage of President Roosevelt in a wheelchair in 2013, to the Cincinnati Enquirer's 2017 piece "Seven Days of Heroin"-illustrate how theoretical concepts work in practice while explaining the new media environment. In response to the lack of awareness of news as mediated narration, Gloviczki calls for journalists to be aware of their role in meaning-making and the attendant ethical responsibilities. He provides the analysis essential to effective practice that emphasizes the connection between the individual and the community in order to more fully represent the mediated body. "--